Impact of Sleep Deprivation on Emotional Regulation and the Immune System of Healthcare Workers as a Risk Factor for COVID 19: Practical Recommendations From a Task Force of the Latin American Association of Sleep Psychology - Almondes, Katie Moraes de; Marín Agudelo, Hernán Andrés; Jiménez-Correa, Ulises (Frontiers in Psychology, 2021)
Healthcare workers who are on the front line of COVID-19 and are also undergoing shift schedules face long work hours with few pauses, experience desynchronization of circadian rhythm, and an imbalance between work hours effort and reward in saving lives, resulting in an impact on work capacity, aggravated by the lack of personal protective equipment (PPE), few resources and precarious infrastructure, fear of contracting the virus and contaminating family members. Some consequences are sleep deprivation, chronic insomnia, stress-related sleep disorders, and post-traumatic stress disorder. These sleep alterations critically affect mental health, precipitating or perpetuating anxiety, stress, and depression, resulting in the inability to regulate positive and negative emotions. Pre-existing sleep disorders are an important risk factor for the development and maintenance of PSTD when individuals are exposed to an important stressor such as a COVID-19 pandemic. At the same time, how an individual regulates the emotion associated with worries during daytime functioning impacts nighttime sleep, precipitating and perpetuating difficulties in sleeping. All of these changes in sleep and emotional regulation also alter the immune system. Sleep deprivation is commonly associated with chronic inflammatory diseases, due to the desynchronizations in circadian rhythms, causing possible psychophysiological disorders and impaired neuroimmune-endocrine homeostasis. From this perspective, we clarify in this article how sleep disorders affect the immune system and emotional regulation, explaining their phenomenological and neurobiological mechanisms, and discussing elements of cognitive and behavioral coping for health professionals to adopt and manage a healthier sleep pattern in the COVID-19 outbreak.